First record of the dinoflagellate Prorocentrum borbonicum in the continental coast of Colombian Caribbean: A new 42 hydroxi-palytoxin producer - Arteaga-Sogamoso, Edgar; Riobó, Pilar; Rodríguez, Francisco; Mancera-Pineda, José Ernesto; Franco-Angulo, Julián (Frontiers in Marine Science, 2022)
The dinoflagellate genus Prorocentrum includes several harmful toxigenic species, predominantly benthic ones. In the past, fast-acting toxicity in mice has been observed in extracts of the epibenthic species P. borbonicum, with the finding of two compounds termed as borbotoxins-A and -B. The presence of palytoxin-like compounds was also suggested from electrophysiological experiments. In the present study, a strain of P. borbonicum was isolated in the continental coast of Colombian Caribbean, in seagrass beds of Thalassia testudinum in Bonito Gordo, Tayrona National Natural Park (PNNT). The morphological and molecular characteristics were consistent with the original and former descriptions for this species. Typical haemolytic activity due to palytoxin was confirmed in P. borbonicum extracts in presence of ouabain, the toxin contents being estimated as 1.9 pg palytoxin equivalents cell-1. HPLC-HRMS analyses of these extracts unambiguously identified the presence of borbotoxins and 42-hidroxy-palytoxin (42-OH-PLTX). This is the first report of palytoxin-like compounds in another dinoflagellate genus than Ostreopsis and the first record of P. borbonicum in Colombia and the Caribbean region.